Reconstructing a Theory of Mind in the Mengzi - Kevin James TURNER (Asian Studies, 2024)
This article reconstructs a theory of mind in the Mengzi 孟子. It argues that recent studies in favor of mind-body dualism import Cartesianism through the vocabulary their arguments are couched in. This article exposes this “Cartesian language game” in order to effect a gestalt shift in our understanding of Mengzian philosophy. It then appeals to John Dewey’s conception of mind as both “minding” and “discourse” where mind is a function of attentive engagement predicated on a background of traditional values and meanings. This article then shows how the Mengzi’s concepts of ren 仁 and tian 天 contribute to a theory of mind where the former is defined as xin 心 thus to be understood as “mindful engagement” and the latter implies tradition as shared reservoir of social and cultural meaning. Through the interpretive comparison of the philosophies of the Mengzi and Dewey, we can reconstruct a Mengzian theory of mind.